Learning from China? Manufacturing, investment, and technology transfer in Nigeria - Chen, Yunnan; Sun, Irene Yuan; Ukaejiofo, Rex Uzonna; Xiaoyang, Tang; Bräutigam, Deborah (International Food Policy Research Institute, 2016)
The question of how to promote structural transformation is central in fostering sustainable growth and poverty reduction in low-income countries in Africa. Following China’s domestic economic transformation and its growing outward investments in the developing world, we seek to understand how Chinese investment in Africa, particularly in manufacturing, may help to foster industrialization and in turn the structural transformation of African economies. We focus on Chinese investments and partnerships in Nigeria, a salient destination for Chinese manufacturing foreign direct investment in Africa, and examine the potential mechanisms of technology transfer that might catalyze such transformation. We find some small but significant cases of potential technology transfer, particularly through technical partnerships between firms. However, the future potential of such mechanisms will depend on the initiative of Nigerian actors to leverage Chinese investment to their interest.